The World Health Organization, Corporate Power, and the Prevention and Management of Conflicts of Interest in Nutrition Policy; Comment on "Towards Preventing and Managing Conflict of Interest in Nutrition Policy? An Analysis of Submissions to a Consultation on a Draft WHO Tool" - Gary Jonas Fooks; Charlotte Godziewski (Kerman University of Medical Sciences, 2022)
The World Health Organization's (WHO's) draft Decision-Making Process and Tool to assist governments in preventing and managing conflicts of interest in nutrition policy marks a step-change in WHO thinking on large corporations and nutrition policy. If followed closely it stands to revolutionise business-government relations in nutrition policy. Ralston and colleagues outline how the food and beverage industry have argued against the decision-making tool. This commentary expands on their study by setting industry framing within a broader analysis of corporate power and explores the challenges in managing industry influence in nutrition policy. The commentary examines how the food and beverage industry's collaboration and partnership agenda seeks to shape how policy problems and solutions are interpreted and acted on and explores how this agenda and their efforts to define conflicts of interest effectively represent non-policy programmes. More generally, we point to the difficulties that member states will face in adopting the tool and highlight the importance of considering the central role of transnational food and beverage companies in contemporary economies to managing their influence in nutrition policy.